Classical sociological theory : rediscovering the promise of sociology - Goodwin, Glenn A.; Scimecca, Joseph A. (Blackwell : USA, 2007)
[This book] reflects sixty-plus years of experience teaching required undergraduate and graduate courses on classical sociological theory. It is a subject matter that both [authors] continue to feel passionately about, and one that [they] feel currently lakcs a text that can both create a similar passion for classical theory in students and present the substantive ideas of the founding men and women of sociology.... [This] text overcomes these limitations. -Pref.
Roots of sociology, morals, and science -- August Comte (1798-1857) -- Harriet Martineau (1802-1876) -- Karl Marx (1818-1883) -- Herbert Spencer (1820-1903) -- Emile Durkheim (1858-1917) -- Georg Simmel (1858-1918) -- Max Weber (1864-1920) -- George Herbert Mead (1863-1931) -- Jane Addams (1860-1935) -- William Edward Burghardt (W.E.B.) De Bois (1868-1963) -- Classical American sociology and the promise of sociology -- Glossary of terms.
Includes bibliographical references and index.
Keywords: Sociology -- History; Sociology -- Methodology -- History; Sociologists -- Biography